Economic Performance in Tanzania: Role of Investments and Financial Development - Kembo Bwana (International Journal of Management, Accounting and Economics)
The study investigates influence of investments and development of financial sector on performance of economy. Secondary data from the year 1997 to 2020 were used in the analysis. The analysis used bounds test for Autoregressive Distributed Lags (ARDL) Model and Error correction model due to existence of co-integrating equations among variables in the long run. Findings indicate existence of co-integrating equations over the long run between the variables. Error correction term is -1.8080 with significant probability of 0.000 implying almost 1.81 percent of deviations between long run values and short run values are adjusted within a year. Findings also revealed that a percentage change in total deposits is associated with 2.13 percent increase in economic performance on average ceteris peribus at 5 percent level of significance. On the other hand, a percent change in capital formation is associated with 0.55 decline in economic performance on average ceteris peribus at 5 percent level of significance. In short run, financial development lagged by one and two years are significantly associated with regress in current year financial progress. As far as investment is concern, one year lagged value is associated with progress of current year investment. The study recommends that financial policies of the country should be crafted in a proactive way taking into consideration that previous years development initiatives in the sector may exhibit negative impact on the current year’s initiatives.